Activity -based method of cost and its role in cost control An applied study on some governmental institutions - ibrahim ahmad, mohamed elbachir (Journal of Research in Finance and Accounting, 2019)
The study aims to determine the impact of the activity -based method of cost on cost control by applying it to some governmental institutions from the point of view of respondents, as well as to know the extent of the respondents' tendency to control costs in government institutions. One of the most important findings of the study is that the use of activity -based method of cost in the institutions helps to achieve cost control. In addition, the participation of the different administrative levels in the application of the activity -based method of cost helps to determine costs in a fair and accurate manner.